Suicidal Behavior in Alcohol Dependence Syndrome - Linus Francis (Asian Journal of Medical Research, 2021)
Background: This study was designed to find the prevalence of suicidal behavior in patients with alcohol dependence syndrome (ADS) and to assess the risk factors for the same. Subjects and Methods: All the patients with ADS who presented during the study period were screened. ADS were diagnosed as per ICD-10 criteria. All the patients underwent detailed clinical and neuropsychiatric evaluation. MINI Scale (Mini International Neuropsychiatry Interview) was used to assess suicidality and BPRS (Brief Psychiatric Rating Scale) was used to assess psychiatric comorbidities. Results: Of the 100 patients with ADS identified during the study period, 14 (14%) had past history of attempted suicide. Conclusion: Patients with psychiatric comorbidity were more likely to have a history of past suicide attempt. The patients with psychiatric comorbidity also had higher current suicidality scores. All patients with alcoholism must be evaluated for comorbid psychiatric problems and suicide risk.